Age of rogues rebels, revolutionaries and racketeers at the frontiers of empires - Öztan, Ramazan; Yenen, Alp (Edinburgh University Press, 2021)
In Age of Rogues, leading scholars engage with themes of historical and cultural legacies, contentious interactions within imperial regimes, and the biographical trajectory of men and women who challenged the political status quo of their time.